Stigma, human rights, and the UN Convention on the Rights of Persons with Disabilities - Bartlett, Peter (Springer, 2017)
The United Nations Convention on the Rights of Persons with Disabilities (CRPD) requires that people with disabilities, including those with mental disabilities (be they psychosocial disabilities/mental health problems or learning disabilities), be able to enjoy full human rights without discrimination. This requirement for non-discrimination, coupled with requirements for social inclusion, chime effectively with the aims of the anti-stigma movement. At the same time, the CRPD will introduce tensions with anti-stigma agendas. Its provisions apply only to people who have a disability, creating the risk that people will need to be identified as having a disability to benefit from its provisions, creating the risk of stigma at that point. The CRPD’s fundamental move away from a medical model of disability will also require the development of new social relationships and new ways of thinking by the professionals who have traditionally been important to the anti-stigma movement, creating potential political difficulties for the movement. This paper looks at these synergies and tensions between the Convention provisions and the anti-stigma movement.